Long‐term risk of stroke and its predictors in transient ischaemic attack patients in Germany. (26th December 2019) - Jacob, L.; Tanislav, C.; Kostev, K.
Abstract : Background and purpose: Little is known about the long‐term association between transient ischaemic attack (TIA) and stroke. Therefore, the goal of this study was to analyze the long‐term risk of stroke and associated predictors in a large cohort of TIA patients followed in general practices in Germany. Methods: This study included patients with an initial TIA diagnosis and subsequently followed up in one of 1262 general practices in Germany between January 2007 and December 2016 ( N  = 19 824 patients). The primary outcome of the study was the risk of ischaemic stroke within 10 years of the initial diagnosis of TIA. The secondary outcome was the identification of demographic, clinical and pharmaceutical variables significantly associated with stroke in TIA patients. Results: Within 10 years of the initial TIA diagnosis, 18.3% of individuals were diagnosed with stroke. Age was positively associated with stroke, with hazard ratios ranging from 1.88 in patients aged 51–60 years to 4.00 in those aged >80 years (reference group: patients aged ≤50 years). Furthermore, male sex, hypertension, diabetes mellitus, atrial fibrillation and ischaemic heart diseases had an additional impact on the risk of stroke. Finally, new oral anticoagulants, heparins, diuretics, angiotensin II receptor blockers and platelet aggregation inhibitors were identified as protective factors. Conclusions: In a cohort of almost 20 000 TIA patients, 18.3% were diagnosed with stroke within 10 years after the TIA index event. Several demographic, clinical and pharmaceutical variables significantly predicted the long‐term risk of stroke in TIA patients.